Analysis of the Impact of Digitalization of Financial Statements and Internal Control on Report Accuracy and Shareholder Trust in Public Companies in Indonesia - Judijanto, Loso; . G, Samsu; Iskandar, Deni (Westscience Press, 2024)
This study examines the impact of financial statement digitalization and internal control on report accuracy and shareholder trust in public companies in Indonesia. Employing a quantitative approach with 240 samples, data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings indicate that digitalization significantly enhances shareholder trust by improving the transparency and accessibility of financial information. Internal control emerges as a key factor in ensuring report accuracy, which indirectly strengthens shareholder confidence. The results underscore the need for public companies to integrate digital tools with robust internal controls to achieve high-quality financial reporting and foster stakeholder trust. This study contributes to the theoretical understanding of digitalization and governance while offering practical insights for improving corporate transparency in emerging economies.